Veterans, the hidden wounds of war, and soul repair: Veteranen, die verborgene Wunde des Krieges und die Heilung seelischer Verletzungen - Grimell, Jan (Spiritual care, 2018)
To better understand how deployment in war zones and/or combat may inflict emotional wounds upon veterans, researchers, clinicians, and caregivers it was recently started to focus on the concepts of moral and spiritual injuries. Such injuries may remain undiscovered during psychiatric screening for posttraumatic stress disorder. What is often missing, however, is a conceptualization of the part of the self which is implicitly related to emotional wounds caused by moral and spiritual injuries. This article utilizes a number of historical and contemporary conceptualizations of what is called the soul, and their implications for pastoral and spiritual care of emotionally wounded veterans. Moreover, it explores the use of biblical stories in pastoral and spiritual care among veterans suffering from moral and spiritual injuries.